Social and school adjustment of adolescent victims of child mal-treatment in residential child care. - Muela Aparicio, Alexander; Balluerka Lasa, Nekane; Torres, Bárbara (Anales de Psicología / Annals of Psychology, 2013)
The aim of this study was to examine the social and school adjustment of maltreated adolescents during their childhood who were in residential child care. In addition, it aimed at checking whether there were any differences between those minors who were subjected to different protective measures. The study included 318 adolescents from the Basque Autonomous Community belonging to three groups. The first group was composed by 69 (31 women and 38 men) adolescent victims of serious family maltreatment, who were separated from their biological families, and were in residential child care; the second group consisted of 75 (29 women and 46 men) adolescent victims of moderated maltreatment, living with their biological families under treatment. Finally, the third group was formed by 174 nonmaltreated adolescents (95 women and 79 men). The age of the subjects ranged between 13 and 18 years (M = 15.35, SD = 1.68). The results showed that, regardless of the child protective measure, those who had been maltreated during their childhood had greater difficulties in social and school adaptation.